Deconstructing the Gender Stereotypes of the Villainess in Dan Brown’s Inferno - Theodar, Caleb (Information & Media, 2024)
This study intends to contribute to the existing research about modern female villains by delving deeper into the ways that represent the stereotypical pattern in film and literature. This article examines Sienna Brooks, the primary antagonist in Dan Brown’s novel Inferno and its film version. She was Bertrand Zobrist’s lover and resolved to finish his work by unleashing his Inferno virus on humanity. Vis-à-vis, articulating feminist momentum through Sienna’s antagonism to the hero highlights the boundaries of binary oppositions, challenging literary critics and questioning gender bias in literature. Female villains have empowered characters because they are often multidimensional, stronger, and more complex than female heroines, instrumental to the story’s narrative. Brown’s block characterisations make inferences about Sienna Brooks both explicitly and implicitly, replicating Sienna’s thinking style or how she thinks about the world in her mind. The conceptual portrayal of the feminine villain narrative reflects the evolving role of women in plot construction, highlighting the need for nuanced and equitable gender representation in movies.